A Valued Relationship with Nature and Its Influence on the Use of Gardens by Older Adults Living in Residential Care. Issue 3 (2nd July 2016) - Reynolds, Lori
ABSTRACT: While there is growing interest in inclusion of gardens and outdoor spaces in residential care facilities for older adults, these spaces are often underutilized despite many identified, evidence-based benefits. A qualitative study of participant observations with behavior mapping, and individual and focus-group interviews, using a grounded theory methodology was used to understand value versus use of outdoor garden spaces. Individual and focus-group interviews were conducted with 32 residents from two facilities. Results revealed that views of nature are fundamentally important to resident well-being, that access to nature influences facility choice, and use of garden spaces is influenced by the way in which individuals prefer to enjoy nature.